Optimizing sulfur fertilizer application rate for profitable maize production in the savanna agroecological zones of Northern Ghana - Agyin-Birikorang, Sampson; Tindjina, Ignatius; Fugice, Job; Dauda, Haruna W.; Issahaku, Alhaji Rahman; Iddrissu, Mumuni; Singh, Upendra (Journal of plant nutrition, 2022)
Although several studies have established the importance of sulfur (S) in increasing maize productivity in the savanna agroecological zones (AEZs) of northern Ghana, the economically optimum S application rate is still unknown. In a two-year study at eight locations across the AEZs, we determined the economically optimum S application rate for S-deficient soils. We compared eight S application rates, ranging from 0 to 70 kg ha −1 at 10 kg intervals, for optimal maize productivity and profitability. The study identified 30 kg S ha −1 as the minimum rate that resulted in a plant tissue S concentration above the critical level of 0.15%. Although increasing the S application rate resulted in increases in maize grain yield, application of S beyond a rate of 30 kg ha −1 resulted in increases in maize grain yield that were not statistically significant and leveled off at 50 kg S ha −1 . Application rates ≥50 kg ha −1 resulted in a high proportion of the applied S not taken up by the plant and, thus, subject to losses from the soil. Based on agro-input prices at the local level and the farm-gate prices of maize, the greatest potential profit resulting from S application was observed at 30 kg S ha −1 , with a projected average maize yield of between ∼4.2 and 5.3 Mg ha −1 , representing >90% of the observed yield with the highest S application rate of 70 kg ha −1 . Thus, we conclude that, for sustainable and profitable maize production in S-deficient soils of the savanna AEZs of northern Ghana, an S applications rate of 30 kg ha −1 is economically justified.